2021
DOI: 10.1088/1361-665x/abdcff
|View full text |Cite
|
Sign up to set email alerts
|

Cement sensors with acoustic bandgaps using carbon nanotubes

Abstract: Cement is widely used in wellbores to stabilize the steel casing used in wellbore operations for oil and gas production, enhanced geothermal systems and carbon sequestration, and to limit fluid movement between sub-surface strata. Flaws such as microcracks in wellbore cement can lead to leakage along the wellbore compromising wellbore integrity. There is an increasing need for methods to monitor cement crack propagation in wellbore environments. In this study, we develop and report the first cementitious senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Hence, for the rest of the experiments, the 16 vol.% PU and 4.0 wt.% benzoic acid were selected as the reference mix to investigate the impact of benzoic acid and COOH-functionalized MWCNTs on the behavior of the BPC. Before mixing, the polyol was nano-modified utilizing COOH-functionalized MWC-NTs at an optimum dosage of 0.5 wt.% of binder; the optimum dosage was chosen based on previous work [9]. The dispersion procedure was performed following previous work done by Douba et al [10].…”
Section: Mwcnt Properties Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, for the rest of the experiments, the 16 vol.% PU and 4.0 wt.% benzoic acid were selected as the reference mix to investigate the impact of benzoic acid and COOH-functionalized MWCNTs on the behavior of the BPC. Before mixing, the polyol was nano-modified utilizing COOH-functionalized MWC-NTs at an optimum dosage of 0.5 wt.% of binder; the optimum dosage was chosen based on previous work [9]. The dispersion procedure was performed following previous work done by Douba et al [10].…”
Section: Mwcnt Properties Measurementsmentioning
confidence: 99%
“…Before mixing, the polyol was nano-modified utilizing COOH-functionalized MWCNTs at an optimum dosage of 0.5 wt.% of binder; the optimum dosage was chosen based on previous work [ 9 ]. The dispersion procedure was performed following previous work done by Douba et al [ 10 ].…”
Section: Materials and MIX Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2000, Liu et al [18] reported local resonance phononic crystal, the structure can manipulate large wavelength acoustic energy by small size structure [19], broadening the study of low-frequency bandgap [20]. The emergence of the local resonance mechanism broke through the limitations of the traditional Bragg scattering bandgap [21,22] and promoted the research of the local resonance mechanism to generate the bandgap [23,24]. For example, He et al [25] proposed a column structure of locally resonant elastic metamaterial based on composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…A band structure is a graph that describes the propagation of waves at certain frequencies through a parametric sweep, hence showing the band gap. Research has been done to develop equations that determine wave propagation, speed of sound, filling fractions and more equations that govern the design of these materials [6][7][8]. The equations used for our particular simulations are listed in the next section.…”
Section: Introductionmentioning
confidence: 99%